1962
DOI: 10.1083/jcb.14.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Protein Uptake by Isolated Tumor Cells

Abstract: Ferritin, added to the incubation medium of ascites tumor cells, was used as an electron microscopic marker to study the uptake of large protein molecules by morphologically intact cells. A definite uptake could be detected after I hour of incubation in Tyrode bicarbonate solution containing 0.04 to 13.3 mg ferritin/ml. Ferritin was found in a variety of membrane-surrounded structures, suggesting that pinocytcsis and related membrane movements are occurring under physiological conditions and can account for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

1967
1967
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…This vacuolization is considered a common cellular response to a variety of adverse conditions (5) and as an early and at first reversible indicator of cellular injury (3). Furthermore, tumor cells incubated in the presence of ferritin during the occurrence of cell damage develop large peripheral vacuoles containing an appreciable number of marker molecules (42). 4 Similar observations have been made in anoxic liver tissue after injection of colloidal mercury as a marker (38).…”
Section: Hypertonicity and Other Infectionenhancing Proceduressupporting
confidence: 62%
See 3 more Smart Citations
“…This vacuolization is considered a common cellular response to a variety of adverse conditions (5) and as an early and at first reversible indicator of cellular injury (3). Furthermore, tumor cells incubated in the presence of ferritin during the occurrence of cell damage develop large peripheral vacuoles containing an appreciable number of marker molecules (42). 4 Similar observations have been made in anoxic liver tissue after injection of colloidal mercury as a marker (38).…”
Section: Hypertonicity and Other Infectionenhancing Proceduressupporting
confidence: 62%
“…4) which, as we have seen, must be interpreted as a pH artefact due to an increased glycolysis in a medium of high glucose content. The nonphysiological character of the reported nuclear incorporation of DNA (36) also follows from the fact that strong cytoplasmic uptake of ferritin (42) or histones (43) by intact tumor cells is not accompanied by any detectable nuclear localization, whereas marked nuclear staining with fluorescein-labeled histones is seen after exposure of cells to acid media. 2…”
Section: Lack Of Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…This agrees with Klintworth's data (1969). Data on the nitrogen metabolism of tissue culture cells indicated that proteins of the medium were utilized to an important extent by growing normal and tumor cells (Ryser et al 1962), and that the tumor cells might display a greater uptake of whole proteins than most normal cells (Ryser et al 1962). The metabolic potentials of fibroblastic cells have been found to differ with their malignancy, growing rate or site of origin (Klintworth 1969) and to exert possibly profound effects on the phagocytic capabilities.…”
Section: Discussionmentioning
confidence: 99%